The Story of the Fibrin(ogen) αC-Domains: Evolution of Our View on Their Structure and Interactions - Medved, Leonid; Weisel, John W. (Thrombosis and Haemostasis, 2022)
Although much has been established concerning the overall structure and function of fibrinogen, much less has been known about its two αC regions, each consisting of an αC-connector and an αC-domain, but new information has been accumulating. This review summarizes the state of our current knowledge of the structure and interactions of fibrinogen's αC regions. A series of studies with isolated αC regions and their fragments demonstrated that the αC-domain forms compact ordered structures consisting of N- and C-terminal subdomains including β sheets and suggested that the αC-connector has a poly(L-proline) type II structure. Functionally, the αC-domains interact intramolecularly with each other and with the central region of the molecule, first demonstrated by electron microscopy and then quantified by optical trap force spectroscopy. Upon conversion of fibrinogen into fibrin, the αC-domains switch from intra- to intermolecular interactions to form ordered αC polymers. The formation of αC polymers occurs mainly through the homophilic interaction between the N-terminal subdomains; interaction between the C-terminal subdomains and the αC-connectors also contributes to this process. Considerable evidence supports the idea that the αC-regions accelerate fibrin polymerization and affect the final structure of fibrin clots. The interactions between αC-regions are important for the mechanical properties of clots, increasing their stiffness and extensibility. Conversion of fibrinogen into fibrin results in exposure of multiple binding sites in its αC regions, providing interaction of fibrin with different proteins and cell types during hemostasis and wound healing. This heretofore mysterious part of the fibrinogen molecule is finally giving up its secrets.
Keywords: fibrinogen; fibrin; fibrin assembly; fibrinogen αC-domains; αC polymers